Perception of the Nigerian Television Authority and Channels Television Reportage of the Chibok School Girls Abduction Among Residents of South-East Nigeria - Orlu-Orlu, Hyacinth C. (European Scientific Journal, ESJ, 2017)
This study was conducted to find out the perception of the television audience on how the Nigerian Television Authority (NTA) and the Channels Television have so far reported the abduction of over 200 female students at Government Girls Secondary School in Chibok, Borno State of Nigeria. The survey research method was used to carry out the study while the questionnaire served as the measuring instrument. The residents of South- East Nigeria constituted the population of the study from where a sample of 384 was drawn using the creative research systems online sample size calculator. Multi-Stage sampling technique was used to select specific local government areas, wards and households that were studied. Findings revealed that NTA’s reports on the abduction of the Chibok school girls are often in favour of government while Channels Television’s reports on the abduction are often balanced. The credibility level of NTA’s reports on the abduction of the Chibok school girls was rated low while that of Channels Television was highly rated. Based on the findings, it was recommended amongst others that the Nigerian Television Authority (NTA) must wake up and endeavour to properly give account of the girls’ abduction. The report must be devoid of ethnic, religious or political sentiment. Doing this will fundamentally lead to believability, which will consequently raise the credibility level of the reports.